Higher IGFB3 is associated with increased incidence of colorectal cancer in older men independently of IGF1 - Chan, Y.; Alfonso, Helman; Paul Chubb, S.; Ho, K.; Gerard Fegan, P.; Hankey, G.; Golledge, J.; Flicker, L.; Yeap, B. (Blackwell Publishing Ltd, 2018)
© 2017 John Wiley & Sons Ltd. Objective: Insulin-like growth factor 1 (IGF1) has anabolic and growth-promoting effects, raising concerns regarding its potential to promote tumour growth. Circulating IGF1 is bound to binding proteins, which modulate bioavailability of IGF1. This study assessed the associations of IGF1 and its binding proteins 1 (IGFBP1) and 3 (IGFBP3) with cancer risk. Design: A prospective cohort study of 4042 men aged =70 years. Methods: Plasma total IGF1, IGFBP1 and IGFBP3 were measured between 2001 and 2004. Cancer-related outcomes were assessed until 20 June 2013 using data linkage. Analyses were performed using proportional hazards models with death as a competing risk, and adjustments were made for potential confounders. Results are expressed as subhazard ratios (SHR). Results: There were 907 men who were diagnosed with cancer during a median of 9-year follow-up. Of these, there were 359, 139 and 125 prostate, colorectal and lung cancers, respectively. After adjustments, total IGF1 was not associated with the incidence of any cancer, prostate, lung or colorectal cancer. In the fully-adjusted model, higher IGFBP3 was associated with increased incidence of colorectal cancer (SHR = 1.20, 95% CI 1.01-1.43; P = .041 for every 1 standard deviation increase in IGFBP3) but not other cancers. This effect was not attenuated by inclusion of total IGF1 into the multivariate model (SHR = 1.28, 95% CI 1.03-1.58; P = .025). Neither total IGF1, IGFBP1 nor IGFBP3 were associated with cancer-related deaths. Conclusion: Higher IGFBP3 predicted increased incidence of colorectal cancer in older men independent of conventional risk factors and total IGF1. Further studies are warranted to explore potential underlying mechanisms.